Uncovered Interest Parity in Crisis : The Interest Rate Defense in the 1990s - Rose, Andrew; Flood, Robert (Washington, D.C. : International Monetary Fund, 2001)
This paper tests for uncovered interest parity (UIP) using daily data for 23 developing and developed countries through the crisis-strewn 1990s. We find that UIP works better on average in the 1990s than in previous eras in the sense that the slope coefficient from a regression of exchange rate changes on interest differentials yields a positive coefficient (which is sometimes insignificantly different from unity). UIP works systematically worse for fixed and flexible exchange rate countries than for crisis countries, but we find no significant differences between rich and poor countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet